Role of the N-glycolylation of mycobacterial peptidoglycan in host immune recognition and antibiotic resistance - Silveiro, Cátia Raquel Lopes (2021)
Tese de mestrado, Ciências Biofarmacêuticas, 2021, Universidade de Lisboa, Faculdade de Farmácia.